2018
DOI: 10.1001/jamapsychiatry.2018.2538
|View full text |Cite
|
Sign up to set email alerts
|

Association of Age at Onset and Longitudinal Course of Prefrontal Function in Youth With Schizophrenia

Abstract: IMPORTANCEThe extent of cognitive deterioration after schizophrenia (SZ) onset is poorly understood because prior longitudinal studies used small samples of older individuals with established illness. OBJECTIVE To examine the association of age at onset and subsequent longitudinal course of prefrontal activity during the first 2 years of illness in youths with SZ and healthy control participants (HCs). DESIGN, SETTING, AND PARTICIPANTSThis naturalistic, longitudinal, functional magnetic resonance imaging (fMRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 72 publications
6
14
0
2
Order By: Relevance
“…Taken together, most of the included studies reported findings of hypoactivation in several brain areas during the basal assessment. Different studies found hypoactivation in the prefrontal cortex (PFC) areas [23, 24, 27, 29, 30, 33, 34] and limbic regions, specifically the amygdala and hippocampus [24, 29, 32, 34]. Hypoactivation was also found in regions such as the basal ganglia, particularly the striatum [24, 26, 31], anterior cingulate cortex (ACC) [23, 24], thalamus [24, 29], bilateral precuneus [29] and posterior cingulate cortex (PCC) [34] (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Taken together, most of the included studies reported findings of hypoactivation in several brain areas during the basal assessment. Different studies found hypoactivation in the prefrontal cortex (PFC) areas [23, 24, 27, 29, 30, 33, 34] and limbic regions, specifically the amygdala and hippocampus [24, 29, 32, 34]. Hypoactivation was also found in regions such as the basal ganglia, particularly the striatum [24, 26, 31], anterior cingulate cortex (ACC) [23, 24], thalamus [24, 29], bilateral precuneus [29] and posterior cingulate cortex (PCC) [34] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al [29] reported several hypoconnected areas across the brain in their global approach to image processing. Niendam et al [27] studied the DLPFC using a task, with a long interval between scans (15 months) and they reported the absence of deterioration during the first 2 years of the illness in a very young patients sample.In contrast, Anticevic et al reported stability of the DLPFC disfunctions starting with the youngest sample that we included in this review. The interpretation of these results is based on the neurodevelopmental hypothesis of schizophrenia, in which deficits emerge before illness onset.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations